Prospects in NSAID-derived chemoprevention of colorectal cancer. (1st August 2005) - Chell, S.; Patsos, H.A.; Qualtrough, D.; H-Zadeh, A.M.; Hicks, D.J.; Kaidi, A.; Witherden, I.R.; Williams, A.C.; Paraskeva, C.
Abstract : There is strong evidence for an important role for increased COX (cyclo-oxygenase)-2 expression and PG (prostaglandin) E2 production in colorectal tumorigenesis. PGE2 acts through four E-prostanoid receptors (EP1–4). COX-2 has therefore become a target for the potential chemoprevention and therapy of colorectal cancer. However, any therapeutic/preventive strategy has the potential to have an impact on physiological processes and hence result in side effects. General COX (COX-1 and -2) inhibition by traditional NSAIDs (non-steidal anti-inflammatory drugs), such as aspirin, although chemopreventive, has some side effects, as do some conventional COX-2-selective NSAIDs. As PGE2 is thought to be the major PG species responsible for promoting colorectal tumorigenesis, research is being directed to a number of protein targets downstream of COX-2 that might allow the selective inhibition of the tumour-promoting activities of PGE2, while minimizing the associated adverse events. The PGE synthases and E-prostanoid receptors (EP1–4) have therefore recently attracted considerable interest as potential novel targets for the prevention/therapy of colorectal cancer. Selective (and possibly combinatorial) inhibition of the synthesis and signalling of those PGs most highly associated with colorectal tumorigenesis may have some advantages over COX-2-selective inhibitors.